Pola Kepemimpinan Hindu Dalam Teks Gaguritan Niti Raja Sasana - I Wayan Sudiarta (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2020)
The Gaguritan text of Niti Raja Sasana contains a leadership pattern that describes the duties as a leader. However, in its current application, there has been a shift in leadership patterns, the Hindu community in general, not many people know the teachings of this leadership. So it is deemed necessary to conduct research related to leadership patterns in the Gaguritan text of Niti Raja Sasana. The method in this research uses literary research methods with mitopic and mimetic approaches. the type of data used is qualitative, primary and secondary data sources. The data collection method used is the method of recording documents or literature. The data processing method is descriptive with induction and argumentation techniques. The Gaguritan text of Niti Raja Sasana which was the object of the study was a text written in a Lontar entitled Niti Raja Sasana. This text is packaged in Gaguritan form which uses several kinds of Pupuh. The leadership patterns contained in the Gaguritan text of Niti Raja Sasana include Asta Brata.Keywords: Hindu Leadership Pattern, Gaguritan Niti Raja Sasana